Spatial Analysis of Green Areas in Al-Assad Suburb (Damascus University Journal of agriculture sciences, 2023)
This research dealt with the spatial analysis of green areas in the Al-Assad Suburb area in Damascus countryside by studying the geographical distribution of green areas and their services, cartographic and statistical analysis of their distribution in the suburban islands and at the sub-island level, and measure their efficiency using GIS and satellite image.The two indicators of Average Nearest Neighbor Distance and Multi Distance Spatial Cluster Analysis showed that the green areas are distributed according to different patterns, whether at the island level or under the islands and at a different level of significance between them. The islands and under the islands are between the random pattern and the divergent pattern. The Multi Distance Spatial Cluster Analysis results confirmed these distribution patterns, emphasizing the importance of the distances between them. The results of the standard Division showed that the green areas are far from the center of the studied area.The number and green areas were also calculated at the levels of the study. At the end of the research, several proposals and recommendations were put forward indicating the need to address the problems that hinder the performance of green areas service and find appropriate solutions to them.
Keywords: GIS; Spatial Analysis; Green Areas, Average Nearest Neighbor; Multi Distance Spatial Cluster Analysis